Nanocomposites based on MWCNT and polystyrene, styrene‐acrylonitrile copolymer, or polymethylmethacrylate, obtained by miniemulsion polymerization. Issue 23 (12th July 2014) - Donescu, Dan; Corobea, Mihai Cosmin; Petcu, Cristian; Spataru, Catalin Ilie; Ghiurea, Marius; Somoghi, Raluca; Gabor, Raluca; Thomassin, Jean‐Michel; Alexandre, Michaël; Jerome, Christine
ABSTRACT Free radical miniemulsion polymerization of styrene (St), St/acrylonitrile 3 : 1 mixture or methylmethacrylate in the presence of multiwalled carbon nanotubes (MWCNT) was proven as a convenient way to obtain homogenous hybrids with perspectives in associated applications like foams specialties materials. Miniemulsion polymerization was viable up to 2% wt. MWCNT to monomer, without agglomerations. The grafting on MWCNT during the polymerization occurs without the need for supplementary functionalization and the polymer grafted nanotubes showed stable dispersions in the polymer solvent. Monomer polarity affected the grafting ability during the polymerization process. The nanocomposites obtained after purification and drying were used in foaming process. MWCNT presence in the related nanocomposites decreased the pore sizes in foam‐like materials (for all three different matrices). At 1 wt % MWCNT content, low density (< 0.3 g/cm3), low pore size (< 10 μm) and high cell density (>109 cell/cm3) were achieved. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41148.